2017
DOI: 10.1080/14786419.2017.1278594
|View full text |Cite
|
Sign up to set email alerts
|

Acclimatization study of Tagetes lucida L. in Egypt and the chemical characterization of its essential oils

Abstract: Seeds of Tagetes lucida were imported to Egypt from Canada and propagated under greenhouse conditions in peat moss media. Soil was sandy in texture and the irrigation system was dripping irrigation. The growth parameters were determined at five successive plant ages, fresh and dry weights of herb were determined at three successive plant ages. The yield of aerial parts after 175 days, was about 7.5 Mg/ha. The essential oil (EO) was extracted by hydro-distillation for three hours with a yield of about 0.5% (w/v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Other compounds include linalol (0.3–3.7%), myrcene (1.3%), ( E )-β-ocimene (2.9%), linalol (1.1%), β-caryophyllene (0.5–2.4%), germacrene D (tr–5.4%), methylisoeugenol (tr–3.9%), bicyclogermacrene (0.6%), spathulenol (tr–0.2%), and caryophyllene oxide (tr–10.3%). These data were confirmed by later papers; an EO distilled from aerial parts from Colombia [ 95 , 96 ] displayed methylchavicol (92.1%), β-myrcene (5.9%), ( E )-β-ocimene (1.3%), and linalol (0.3%), while an EO from Egypt [ 97 ] contained over 90% methyl chavicol.…”
Section: Phytochemical Composition Of Eos Obtained From supporting
confidence: 58%
“…Other compounds include linalol (0.3–3.7%), myrcene (1.3%), ( E )-β-ocimene (2.9%), linalol (1.1%), β-caryophyllene (0.5–2.4%), germacrene D (tr–5.4%), methylisoeugenol (tr–3.9%), bicyclogermacrene (0.6%), spathulenol (tr–0.2%), and caryophyllene oxide (tr–10.3%). These data were confirmed by later papers; an EO distilled from aerial parts from Colombia [ 95 , 96 ] displayed methylchavicol (92.1%), β-myrcene (5.9%), ( E )-β-ocimene (1.3%), and linalol (0.3%), while an EO from Egypt [ 97 ] contained over 90% methyl chavicol.…”
Section: Phytochemical Composition Of Eos Obtained From supporting
confidence: 58%
“…Our result corroborates a report by Regalado et al, [10], which identified forty volatile compounds and estragole was the major constituent with a 96.8% composition. The analysis of EO from T. lucida plants from Egypt [11,12], Colombia [13], and Costa Rica [14] also showed that the main component identified was estragole, corresponding to more than 80% of the entire composition. Therefore, it appears that this chemotype is highly predominant, for which this plant has been recommended as a relevant source to obtain pure estragole [14].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, a different quantitative and qualitative composition has also been documented in plants collected from Mexico [15], in which the main compound was geranyl acetate (49.9%). A perusal of the literature reveals at least four different chemotypes of T. lucida based on essential oil composition: (1) an estragole-dominated chemotype [10][11][12][13][14], (2) an estragol/anethol chemotype [15,16], (3) a methyl eugenol chemotype [17], and (4) a geranyl acetate-rich chemotype [17,18]. The phenylpropanoid estragole is found in numerous EOs and is known to possess different pharmacological properties, such as antifungal [19], antiparasitic [20,21], and anti-inflammatory [22] activity.…”
Section: Resultsmentioning
confidence: 99%